A multicenter, randomized, open-label, comparative, phase IV study to evaluate the efficacy and safety of combined treatment with mycophenolate mofetil and corticosteroids in advanced immunoglobulin A nephropathy - Sang Youb Han; Chan-Young Jung; Sang Ho Lee; Dong Won Lee; Sik Lee; Chan-Duck Kim; Bum Soon Choi; Beom Seok Kim (The Korean Society of Nephrology, 2022)
Background It remains unclear whether immunosuppressive agents are effective in patients with immunoglobulin A nephropathy (IgAN). We investigated the efficacy of a mycophenolate mofetil (MMF) and corticosteroid combination therapy in patients with advanced IgAN. Methods We conducted a multicenter, randomized, placebo-controlled, parallel-group study of 48 weeks administration of MMF and corticosteroids in biopsy-proven advanced IgAN patients with estimated glomerular filtration rate (eGFR) of 20-50 mL/min/1.73 m2 and urine protein-to-creatinine ratio (UPCR) of >0.75 g/day. The primary outcome was complete (UPCR < 0.3 g/day) or partial (>50% reduction of UPCR compared to baseline) remission at 48 weeks. Results Among the 48 randomized patients, the percentage that achieved complete or partial remission was greater in thecombination therapy group than in the control group (4.2% vs. 0% and 29.1% vs. 5.0%, respectively). Compared with the combination therapy group, eGFR in the control group decreased significantly from week 36 onward, resulting in a final adjusted mean change of -4.39 ± 1.22 mL/min/1.73 m2 (p = 0.002). The adjusted mean changes after 48 weeks were 0.62 ± 1.30 and -5.11 ± 1.30 mL/min/1.73 m2 (p = 0.005) in the treatment and control groups, respectively. The UPCR was significantly different between the two groups; the adjusted mean difference was -0.47 ± 0.17 mg/mgCr and 0.07 ± 0.17 mg/mgCr in the treatment and control group, respectively (p = 0.04). Overall adverse events did not differ between the groups. Conclusion In advanced IgAN patients with a high risk for disease progression, combined MMF and corticosteroid therapy appears to be beneficial in reducing proteinuria and preserving renal function.